Innovative Activities and Sustainability Standards for Acquisition and Retention of Tea Markets in Southern Highlands of Tanzania (Global Journal of Management and Business Research, 2020)
Since 2013, the Government of Tanzania has put in place an agricultural policy that emphasizes sustainable agriculture through sustainable, environmentally friendly crop husbandry practices and public-private collaboration with other agricultural marketing actors in meeting product quality, grades and standards for domestic, regional and international markets. This paper, therefore, assessed the influence of Innovative Activities on Sustainability Standards for Acquisition and Retention of tea markets in the Southern Highlands of Tanzania. It specifically intended to determine the extent of innovative activities undertaken by the tea growers in obtaining and maintaining certified compliance of tea sustainability standards; examine the influence of activities on sustainability standards; and examine the power of sustainability standards on acquisition and retention of tea markets in Southern Highlands of Tanzania. The data were collected using a questionnaire from 300 tea growers sampled through a stratified random sampling technique.
Keywords: innovative activities; sustainability standards; acquisition and retention of markets